Phenomenological Studies: Utilization of the Social Environment as a Source of Social Studies Learning in Elementary Schools - Tapung, Marianus (Journal of Comprehensive Science, 2025)
The research aims to explore the experiences of teachers and students in utilizing the social environment as a learning resource for Social Science (IPS) subjects. Using a qualitative approach with a phenomenological method, this study involved eight social studies teachers and sixteen students in grades V-VI from four elementary schools in Manggarai Regency. Data were collected through in-depth interviews, participatory observations, and documentation reviews, focusing on understanding the essence of the experiences experienced by participants. The selected schools reflect the diversity of demographic and sociocultural characteristics of the Manggarai region, so the study results are expected to provide a comprehensive picture of social environment-based learning practices. Through semi-structured interviews, the researcher explored the meanings that emerged from the participant's experiences in the context of social studies learning. This research is expected to contribute to developing more effective learning methods by utilizing the social environment as a learning resource and increasing students' understanding of the material taught. The research results will be a reference for developing curriculum and learning strategies in elementary schools.